2022
DOI: 10.3390/healthcare10122349
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes of a Remote Digital Musculoskeletal Program: An Ad Hoc Analysis from a Longitudinal Study with a Non-Participant Comparison Group

Abstract: Digital solutions have emerged as an alternative to conventional physiotherapy, particularly for chronic musculoskeletal pain (CMP) management; however, its long-term effects remain largely unexplored. This study focuses on patients reporting CMP, assessing 1-year clinical outcomes after a multimodal digital care program (DCP) versus non-participants, who enrolled in the program but never engaged in a single exercise session or partook of the educational content made available to them. In this longitudinal stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 96 publications
0
25
0
Order By: Relevance
“…The study evaluated the impact of a completely digital program in patients with chronic musculoskeletal pain. Results showed that participants included in the program reported significantly higher improvements in pain and function in comparison to the control group of non-starters at 1-year follow-up [ 117 ].…”
Section: Telemedicinementioning
confidence: 99%
See 4 more Smart Citations
“…The study evaluated the impact of a completely digital program in patients with chronic musculoskeletal pain. Results showed that participants included in the program reported significantly higher improvements in pain and function in comparison to the control group of non-starters at 1-year follow-up [ 117 ].…”
Section: Telemedicinementioning
confidence: 99%
“… Improved access to care even for patients living in areas remote from the clinic through saving the resources and reducing costs at all levels by minimizing the use of PPE, transportation, and traveling [ 16 , 22 ]. It facilitates the communications with those coming from long distances, physically unfit patients with multiple comorbidities, or already-infected patients [ 22 , 117 ]. Some non-pharmacological and physical tools such as patient’s educations, psychological support, medical instructions, exercises, and posture or lifestyle changes can be easily implemented through telemedicine [ 22 , 117 ].…”
Section: Telemedicinementioning
confidence: 99%
See 3 more Smart Citations